Comparison of Desired-Genetic-Gain Selection Indices in Late Generations as an Insight on Superior-Family Formation in Bread Wheat (Triticum aestivum L.) - Rasha Ezzat Mahdy; Zaharh M. A. Althagafi; Rasha M. Al-Zahrani; Hanan H. K. Aloufi; Reem A. Alsalmi; Amany H. A. Abeed; Ezzat Elsayed Mahdy; Suzan A. Tammam (Agronomy, 2022)
Wheat is one of the most important sources of food worldwide. A selection index helps in making selection decisions and permits the exploitation of information on correlated traits to improve yields. Two cycles of pedigree selection based on the desired-genetic-gain selection index were imposed to identify the best index to isolate promising lines. The base population was composed of 120 families of bread wheat in the F6 generation. Eight combinations were constructed from six traits, i.e., days to heading (DH), number of spikes/plant (NS/P), grain yield/plant (GY/P), number of grains/spike (NG/S), mean spike weight (MSW) and mean grain weight (GW). The narrow-sense heritability of NS/P, NG/S, MSW and GW increased from cycle 1 to cycle 2, revealing an increase in the observed gain and homogeneity of the selected families for these traits from cycle to cycle. After the second cycle, the observed gain in GY/P ranged from 9.5 to 23.75% of the mid-parent. The best index for improving GY/P was index 2 (composed of GY/P, NS/P, NG/S, MSW and GW). The indices involving DH were inferior for improving GY/P. The desired-genetic-gain index was efficient in simultaneously improving several involved traits and was a good method to preserve genetic variability. Furthermore, six superior promising families were identified.